Bilateral Deficit in Countermovement Jump and Its Influence on Linear Sprinting, Jumping, and Change of Direction Ability in Volleyball Players - Pleša, Jernej; Kozinc, Žiga; Šarabon, Nejc (Frontiers in Physiology, 2022)
We assessed the association between bilateral deficit (BLD) in countermovement jump (CMJ) and change of direction (CoD) performance, CoD deficit, linear sprinting and approach jump tasks. The participants (47 young volleyball players; age: 20.8 ± 3.8 years) performed bilateral and single-leg CMJs, modified T-test, 505 CoD test, 25-m sprints (with 5,10 and 15 splits) and vertical approach jumps. CoD deficit was also calculated from 505 test and 10 m split time. BLD was calculated from CMJ jump height, peak power and phase-specific force impulses (FI). Several small to moderate statistically significant correlations (r = 0.42 to 0.49) were found between BLD and 505 times (7 correlations), sprint times (4 correlations), CoD deficit (1 correlation) and approach jump (1 correlation). T-test performance was not correlated with BLD variables (r = -0.15-0.22). The direction of the correlations implied that larger BLD is associated with superior performance, with the exception of 1 correlation for 505 time for the left leg and 1 for CoD deficit for the left leg. However, these two variables showed unacceptable reliability. Our results suggest that BLD could be useful for guiding the decisions related to the extent of inclusion of unilateral training for volleyball players.